The Effect of the Number of Employees and the Number of Offices on the Profitability of Islamic Commercial Banks in Indonesia - Yulia Andriani; Leni Riski Hayati; Jhody Wiraputra; Okta Sari (International Publisher, 2025)
This study aims to analyze the effect of the number of employees and the number of offices on the profitability of Sharia commercial banks (BUS) in Indonesia for the period 2020-2024. The research method employed is a quantitative approach, utilizing secondary data in the form of monthly time series data sourced from Islamic banking statistics provided by the Financial Services Authority. Data analysis was performed using multiple linear regression with the help of SPSS version 25.0. The results showed that partially, both the number of employees and the number of offices did not have a significant influence on the profitability of Islamic commercial banks in Indonesia. The implications of these findings indicate that physical expansion and increasing the quantity of human resources are no longer the main determinants of profit in the era of digitalization, so bank management needs to switch to operational efficiency strategies and information technology modernization to improve financial performance.